Disqualification of prisoners' right to vote under Malaysian Federal Constitution: a comparative legal analysis / Hasnatulsyima Abdullah Hadi … [et al.] - Abdullah Hadi, Mat Hasnatulsyima; Ahmad, Nurul Hanani; Muhamad, Suriantiazila; Iskandarshah, Muhammad Izayyeem Azim (2014)
This research focuses on the prisoner's right to vote which is part of democratic rights enjoyed by citizens of Malaysia. Within the context of this research, "prisoner" means a person, who is under confinement in a prison which includes a prisoner released on parole. As at 2013, there were 39,432 prisoners in Malaysia and the number of prisoners is reportedly increasing. Malaysian laws forfeit certain aspects of fundamental rights of prisoners which include the right to vote. By virtue of Article 119(3) of the Federal Constitution, the prisoners are among three categories of Malaysian citizens who lost their electoral rights throughout their term of imprisonments. This research argues that disqualification of prisoner's right to vote goes against the basic tenets of human right and democracy. Hence, it is the aim of this research is to provide a set of recommendation pertaining to the prisoners' right to vote in Malaysia. To achieve this aim, this research has analysed various laws, theories and principles underpinning the prisoners' right to vote. This research contains six chapters focusing among others on the disqualification of prisoners' right to vote, the basis for disqualification of prisoners' right to vote, theories underlying the prisoner's right to vote and legal analysis of the laws pertaining prisoners' right to vote in Malaysia. The concluding chapter provides a set of recommendation pertaining to the prisoners' right to vote based on the input derived from the analysis made on various laws pertaining to prisoners' right to vote.